Anti-HBV drug entecavir ameliorates DSS-induced colitis through PD-L1 induction - Yamamoto, Yuichiro; Carreras, Joaquim; Shimizu, Takanobu; Kakizaki, Masatoshi; Kikuti, Yara Yukie; Roncador, Giovanna; Nakamura, Naoya; Kotani, Ai (Pharmacological research, 2022)
PD-L1-mediated signaling is one of the major processes that regulate local inflammatory responses in the gut. To date, protective effects against colitis through direct Fc-fused PD-L1 administration or indirect PD-L1 induction by probiotics have been reported. We have previously shown that the anti-HBV drug entecavir (ETV) induces PD-L1 expression in human hepatocytes. In the present study, we investigated whether ETV induces PD-L1 expression in intestinal cells and provides a protective effect against DSS-induced colitis. ETV induced PD-L1 expression in epithelial cells, rather than T and B cells, improving the symptoms of colitis. In the mechanistic analysis, Th17 cell differentiation was inhibited and B cell infiltration into the lamina propria was reduced. In addition, PD-L1 expression was positively correlated with Foxp3 or CSF1-R. In conclusion, ETV upregulated PD-L1 expression in epithelial cells and ameliorated inflammation in DSS-induced colitis. These results suggest that ETV may be a potential therapeutic agent as a PD-L1 enhancer for the treatment of human IBD. [Display omitted]